TRANSFER OF ARGOS-LIKE AND ATEXPA10 GENES INTO NONTRANSGENIC FORMS OF TOBACCO AND PHENOTYPIC EFFECTS OF THEIR CONSTITUTIVE EXPRESSION - B. R. Kuluev; E. V. Mikhaylova; A. V. Chemeris (Вавиловский журнал генетики и селекции)
Hybrid plants were obtained by pollination of Nicotiana rustica and Nicotiana tabacum Black Cuban cultivar with pollen of transgenic Nicotiana tabacum plants of Petit Havana SR1 cultivar bearing the ARGOS-LIKE and AtEXPA10 genes. RT-PCR analysis showed high levels of ARGOS-LIKE and AtEXPA10 expression in the hybrids. It led to an increase in the sizes of their leaves and stems. Organs of both transgenic and hybrid plants were enlarged due to the enlargement of individual cells. The inheritance was stable, but the phenotypic effects varied from insignificant to levels exceeding those in parental transgenic plants.